Penerapan Hukum Wakaf Uang di Indonesia Perspektif Legal System Theory - Masdar, Masdar (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
Cash waqf in Indonesia has been long enough implemented based on some rules enacted by government and other rules defined by The Waqf Board of Indonesia (BWI). However, the implementation of cash waqf has not reached the level of success. Therefore, this article studies the application of cash waqf law in Indonesia according to Friedman’s legal system theory. The legal system theory of Friedman firstly looks at the substance of the law, which is the rules or regulations; and secondly it examines the structure of the law, encompassing the law enforcement agencies, such as judge, prosecutor, police and legal counselors. And lastly the theory examines the element of legal culture, which is a response from Muslim society. The first two examinations indicate that there is nothing to be a problem. But from the last examination there is a problem regarding the trust from Muslim society. From the legal culture point of view, the implementation of cash waqf by the government, which is performed by BWI, needs attracting society’s credentials in order to improve and maximize the performance of cash waqf in Indonesia.